(untitled) (Archives of Criminology, 2025)
In this article, I reinforce Albert K. Cohen’s theory with selected psychological theories. Cohen’s concept may seem outdated today, as it presents a twentieth-century social structure. A comparison between the theory of delinquent subcultures and psychological theories brings to light similarities and convergences between the theses put forward by Cohen and the remarks of more contemporary authors. These analogies make it possible to present the concept of delinquent subcultures in the form of a model that could be empirically verified in the future. The similarities I discuss include issues of self-esteem, status, aggression, and adjustment.